Protecting women’s interest (Maslahah) in marriage through appointment of a guardian (wali) under Islamic law - Mohd, Azizah; Ibrahim, Badruddin; Abdul Razak, Syafiqah (UPM Press, 2015)
Waliin general refers to a person who consents or leads a marriage contract. Under the majority school of law (jumhur) including the Shafi’is, wali constitutes one of the pillars of marriage the absence of whom will render the marriage void. On the other hand, under the Hanafischool of law, wali is not a pillar but merely one of the conditions for execution of a marriage contract. Even though under the Hanafischool, the absence of wali does not seem to render the marriage invalid so long as the marriage fulfills some other conditions and the wali does not intervene in the marriage of his ward. Nevertheless, this condition does not seem to deny the importance of wali in the marriage of his ward. This paper is to highlight and emphasize on the fact that the appointment of wali in marriage of a woman is significantly to protect women’s or wards welfare (maslahah). The paper among others wishes to examine the importance and wisdom of having wali in marriage of a woman and exploring further the reason why the presence or consent of a wali is considered crucial particularly under the majority school of law. Examination will extend to analysis on the requirement of wali under the law in Malaysia and several Muslim Countries to serve as comparison. The research is basically library research. Minor part of the research involve interviews on certain opinions of the scholars on the importance of having wali in marriage. It is believed that this research will significantly contribute to knowledge especially in disclosing the philosophy and wisdom of having guardian (wali) in marriage of a woman under Islamic law while many Muslim women nowadays (with special reference to Malaysia) seem to disregard wali while contracting their marriage.